Pengaruh Perkembangan Teknologi Terhadap Kebugaran Jasmani Pada Generasi Alpha - Apriyanti, Linda Salsa; Mulyana, Agus; Rahmadewi, Anzani; Tarigan, Emia Rita Pitriani; Zakiyah, Hana; Sumarni, Rindi; Nurkamila, Risma (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Research focused on analyzing the extent to which technological developments affect the physical fitness level of gen alpha. The research uses a qualitative method by relying on various literatures. The data in this study were obtained through literacy studies as analysis techniques. Gen alpha’s a physical development has an influence from technological development. Gen alpha grew up in the middle of the digital era and is accustomed to technological sophistication. Physical fitness has benefits for health which aims to prevent the body from feeling excessively tired due to the activities that human do because it needs to be accompanied by sufficient energy. The results showed that technological development affected the level physical fitness of alpha genes. Physical fitness is very important for children’s activities and the influence of technology makes gen alpha rarely do physical activities. This causes physical fitness to slowly decrease, so the little physical activity they do makes them feel tired. Thus, knowing the extent to which technological development affects the physical fitness of gen alpha can be a reference for parents and teachers to direct children to carry out physical activities that can improve physical fitness.